PENINGKATAN KEMAMPUAN PANTAU PERTUMBUHAN, KECERDASAN DAN KESEHATAN MENTAL ANAK SEKOLAH PADA ORANG TUA SISWA DI SDN KEDAUNG BARAT 1, TANGERANG (Jurnal Pengabdian Masyarakat AbdiMas, 2022)
This community service activity is based on the lack of understanding of the factors that influence growth, comprehension of the types of intelligence and mental health of school-age children among parents. The aims of this activity is to improve participants' understanding of factors that affect growth, measurement procedure, assessment of intelligence types and children's mental health. This multidisciplinary activity was carried out in December 2021 and involved as many as 22 parents/guardians of the Kedaung Barat State Elementary School 1. Participants agreed to be given online education (zoom meeting) followed by pre-post tests and discussions. There is an increasing understanding of the need for routine growth measurements in an accurate and precise manner. Although it was still found that more than a third to half of the participants did not understand how genetic, infection and hygiene factors could affect growth. Regarding intelligence, all participants understood the role of nutrition for intelligence but most of them still related intelligence to academic areas. More than a third still believe brain size affects intelligence. Regarding children's mental health, most of the participants did not agree that mocking while joking is a common thing for children. Most of the participants agreed to dare to reprimand a child's friend if he mocked another friend. The majority of participants were satisfied with the material presented. However, participants expect for further activities were given face-to-face, especially related to measurement methods, assessment of children's intelligence areas and mental health counseling. Keywords: nutrition, growth, intelligence, mental health.